The Effect of Target Pattern Training on Smash Accuracy in Badminton Sports - Elga Alviyana; Indra Safari; Adang Sudrazat (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of target pattern training on smash accuracy in badminton. Smash accuracy is one of the key factors in the success of badminton, which requires high technical skills and concentration. The method used in this study was an experiment with a pre-test and post-test design. The study sample consisted of 20 badminton athletes who were divided into two groups, namely the experimental group who did target pattern training and the control group who did not receive special treatment. Target pattern training was carried out for 6 weeks with a frequency of 3 times a week. Smash accuracy measurements were carried out before and after the training using a validated smash accuracy test. The data obtained were analyzed using a paired t-test to see the difference in average smash accuracy before and after training. The results showed a significant increase in smash accuracy in the experimental group compared to the control group. Based on these results, it can be concluded that target pattern training has a positive effect on increasing smash accuracy in badminton athletes. The results of the statistical data analysis obtained from the pre-test data test had a P-value (sig) of 0.875. In other words, the test conducted using Kolmogorov Smirnov on the pre-test is greater than α = 0.05, which means that the data is normally distributed. And the paired sample t-test obtained a result of 0.000 <0.05. So it can be concluded that there is an effect of target pattern training on smash accuracy in badminton. The results of the initial and final tests showed that there was a significant increase after the treatment was given. This shows that this target smash pattern training method has an effect on improving the quality of reaction speed for the Badminton Student Activity Unit at one of the Universities in West Java, Sumedang Regency.